POTENTIAL TRIGONA BEEKEEPING (Heterotrigona itama and Geniotrigona thoracica) AT SOUTH LABUHANBATU CITY, NORTH SUMATERA PROVINCE, INDONESIA - Pinandita, Eggi Pur; Minarti, Sri; Junus, Mochammad; Radiati, Lilik Eka; Besari, Ratna Iffany F; Soen, Jopie Meiske; Simanjuntak, Aurora Ivana Br (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2022)
Study area this research was conducted on November 12th – 21st, 2021, located in Kota Pinang, South Labuhanbatu, North Sumatra, Indonesia. The results of this study can provide a report on the results of the analytical test carried out in the laboratory of the University of Brawijaya. South Labuhanbatu Regency is geographically located at 1°26'00'' - 2015'55'' North Latitude. 99°40'00'' - 100°26'00'' East Longitude. Generally, South Labuhanbatu Regency is located at an altitude below 100 meters above sea level. The type of research is exploratory research. The result and discussion gave the best replacement of water content in honey at Apis dorsata as an average of 27%. It showed that the higher the water content and acidity of the honey will explain the lower the quality of the honey. The best replacement levels of sucrose in honey at Heterotrigona itama as an average of 68.5%. The percentage level of sucrose showed that honey with a moisture content of more than 17%, with a total sugar content of <83% is susceptible to cosmetological yeast fermentation. The best pH of Honey placed at Apis dorsata is an average of 2.350 (Acid). The data showed that the low pH value and high acidity can increase the shelf life of honey because it does not support the growth of microbes.